2016
DOI: 10.18632/oncotarget.12778
|View full text |Cite
|
Sign up to set email alerts
|

Generation of CD20-specific TCRs for TCR gene therapy of CD20low B-cell malignancies insusceptible to CD20-targeting antibodies

Abstract: Immunotherapy of B-cell leukemia and lymphoma with CD20-targeting monoclonal antibodies (mAbs) has demonstrated clinical efficacy. However, the emergence of unresponsive disease due to low or absent cell surface CD20 urges the need to develop additional strategies. In contrast to mAbs, T-cells via their T-cell receptor (TCR) can recognize not only extracellular but also intracellular antigens in the context of HLA molecules. We hypothesized that T-cells equipped with high affinity CD20-targeting TCRs would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Transfer of an HLA-B*07:02restricted CD20 epitope-specific TCR enabled recognition of CD20-positive malignant cell lines and primary tumors (CLL, ALL, and mantle cell lymphoma) and suggested that TCR-based approaches may be effective in low-expression CD20-positive B-cell malignancies. 53 T cells transduced with a different TCR specific for an HLA-B*07:02-restricted CD22 epitope killed primary B-cell leukemia cells, but also killed healthy dendritic cells and macrophages, 54 illustrating both the potential promise and limitation of targeting lineage-restricted antigens.…”
Section: Lineage Restrictedmentioning
confidence: 99%
“…Transfer of an HLA-B*07:02restricted CD20 epitope-specific TCR enabled recognition of CD20-positive malignant cell lines and primary tumors (CLL, ALL, and mantle cell lymphoma) and suggested that TCR-based approaches may be effective in low-expression CD20-positive B-cell malignancies. 53 T cells transduced with a different TCR specific for an HLA-B*07:02-restricted CD22 epitope killed primary B-cell leukemia cells, but also killed healthy dendritic cells and macrophages, 54 illustrating both the potential promise and limitation of targeting lineage-restricted antigens.…”
Section: Lineage Restrictedmentioning
confidence: 99%
“…B cell-specific transcription factor BOB1-HLA-B*07:02-TCR-engineered T cells was efficiently shown to lyse primary B-cell leukemia, mantle cell lymphoma, and multiple myeloma in vitro and had in vivo antitumor reactivity in a multiple myeloma xenograft mouse model. This strategy may provide a novel target cellular treatment option for patients with B cell malignancies [41]. HMMR/Rhamm is overexpressed in numerous types of cancer, including ALL and AML.…”
Section: Tcr-t Cells For Leukemia Immunotherapy In Preclinical Studiesmentioning
confidence: 99%
“…Thymic deletion can also be bypassed by using HLA-mismatched donors to generate allo-TCRs specific for a given peptide-MHC [27]. Allogenic TCRs are sensitive enough to target antigens expressed at a very low copy number that cannot be targeted by antibody-based therapies [28]. However, it is crucial to ensure that TCRs procured from allogeneic HLA donors are truly peptidespecific rather that recognising allo-HLA irrespective of the peptide cargo.…”
Section: Bypassing Thymic Selection Yields Highly Sensitive Tcrsmentioning
confidence: 99%